2010
DOI: 10.1038/ejcn.2010.135
|View full text |Cite
|
Sign up to set email alerts
|

The regular consumption of a polyphenol-rich apple does not influence endothelial function: a randomised double-blind trial in hypercholesterolemic adults

Abstract: Background/objectives: Epidemiological studies suggest that apple consumption is associated with a reduction in cardiovascular disease risk. Apple polyphenols may contribute to explain these effects. Endothelial dysfunction has been associated with early stage of atherosclerosis and polyphenols from various dietary sources have been shown to reverse it. The aim of the present study was to investigate the effect of the consumption of a polyphenol-rich apple on endothelial function. Subjects/methods: In all, 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 57 publications
1
47
1
3
Order By: Relevance
“…In disagreement with the previous studies, Auclair et al [55] demonstrated that consumption of a polyphenol-rich apple does not improve vascular function studied by brachial artery FMD in 30 hypercholesterolemic patients who had consumed 40 g of two lyophilized apples, polyphenol-rich and polyphenol-poor, providing respectively 1.43 and 0.21 g polyphenol per day.…”
Section: Endothelial Function and Blood Pressurecontrasting
confidence: 51%
See 1 more Smart Citation
“…In disagreement with the previous studies, Auclair et al [55] demonstrated that consumption of a polyphenol-rich apple does not improve vascular function studied by brachial artery FMD in 30 hypercholesterolemic patients who had consumed 40 g of two lyophilized apples, polyphenol-rich and polyphenol-poor, providing respectively 1.43 and 0.21 g polyphenol per day.…”
Section: Endothelial Function and Blood Pressurecontrasting
confidence: 51%
“…No significant effect was observed on diastolic blood pressure. Therefore the authors concluded that intake of flavonoid-rich apples can augment nitric oxide status, enhance endothelial function, and lower blood pressure acutely, outcomes that may benefit cardiovascular health [55].…”
Section: Endothelial Function and Blood Pressurementioning
confidence: 99%
“…In another study, flavonoid-rich apples with nitrate-poor spinach significantly improved FMD by 1.1% absolute, when compared to a low-flavonoid apple and low-nitrate controls in the fasting state [51]. Conversely, it has previously been shown that FMD is unaffected by the polyphenol content of lyophilised apples (w40 g/d or equivalent to 270 g whole apple/d) after 4 weeks of feeding [52]. Further studies using whole fruit and vegetables are needed to clarify the effect of increasing fruit and vegetable intake on endothelial function.…”
Section: Fruit and Vegetables And Endothelial Vasodilator Functionmentioning
confidence: 81%
“…However, the many different apple cultivars with a wide range of polyphenol contents and profiles provide a large assortment for human studies. A recently published study (Auclair et al, 2010) however with two apple cultivars with different amounts of polyphenols failed to show an influence on endothelial function in humans. The polyphenol profiles from different apple cultivars evaluated in the present study could help in selecting cultivars with different polyphenol patterns for future studies designed to measure the physiological effects of flavan-3-ols or phenolic acid rich apples.…”
Section: Classification Of Apples Based On Their Polyphenol Profilementioning
confidence: 88%